(3OQGSI ebGQfIs - (3eMeO MSf(B, (3ONjds ((3HjQhJ(B:s (3efThQGJ GdMdHj GdMbhbjI(B,s, 2009)
(3OQGSI GTcGdjGJ HMKjI GSGSjI jJYdb GHQRgG HGdJGKjQ GdeJHGOd Hjf GdJfejI hGdSjGSI MjK Hjf GdYdGbI Hjf GdJfejI hGdOjehbQGWjI hGgejI GdJfejI aj GdehGKjb GdOhdjI h GdGbdjejI h GdTQGFY GdOjfjI h aj eQJcRGJ GdfXGe GdSjGSj eY hVY eKGd Mj Ydi GdhGbY GdGfeGFj aj dHfGf(B.s
(3eQGLY U(B.417 (3; edGMb U(B.377s
Keywords: (3GdGbJUGOs; (3GdJfejIs; (3GdJfejI GdGbJUGOjIs